Utilização da acupuntura no tratamento de cães com discopatia intervertebral - Gonçalves, Átila Jorge [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The intervertebral disc diseases have a high casuistic in clinical routines veterinary among dogs. These conditions can cause pain, paresis or paralysis of limbs depending on the degree of injury. Clinical signs are not limited to the intervertebral disc, other anatomical parts are included. In conventional medicine, treatment may be surgical or clinical, by the use of corticosteroids with muscle relaxants. Acupuncture was an alternative to treating these diseases due to its anti-inflammatory and analgesic effects. Although there are few studies for the treatment of discopathies, acupuncture triggers the release of substances such as dynorphins, beta-endorphins and serotonin, among others; that act inhibiting somatic and visceral pain. Electroacupuncture is used to potentiate the effects of acupuncture. It can be performed with different frequencies according to the clinical evolution. However there are different opinions related to the greater efficacy in relation to acupuncture. The restraint and monitoring of the treated animal are important factors for its recovery. The association between acupuncture and conventional treatment (surgical or clinical) achieved better results than acupuncture alone. This proves that acupuncture can be considered an option in order to minimize the complications of surgery or assist in patient recovery

As doenças de disco intervertebral têm uma alta casuística na rotina clínica veterinária entre os cães. Essas afecções podem causar dor, paresia ou paralisia de membros dependendo do grau da lesão. Mas os sinais clínicos não se limitam ao disco intervertebral, outras estruturas estão inclusas. Na medicina convencional, o tratamento pode ser cirúrgico ou clínico por meio da utilização de corticoesteróides com relaxantes musculares. A acupuntura é uma alternativa ao tratamento dessas afecções por seus efeitos analgésicos e antiinflamatórios. Embora existam poucos estudos no tratamento das discopatias, está comprovado que a acupuntura desencadeia a liberação de substâncias como dinorfinas, beta-endorfinas, serotonina, entre outras; que agem inibindo os estímulos dolorosos somáticos e viscerais. A eletroacupuntura é uma modalidade com objetivo de potencializar os efeitos da acupuntura. Pode ser feita com diferentes freqüências de acordo com a evolução do quadro clínico. Mas há opiniões divergentes quanto a sua maior eficácia em relação à acupuntura. O confinamento e monitoração do animal no tratamento são importantes para a recuperação do animal. A associação entre a acupuntura e o tratamento convencional (cirúrgico ou clínico) obteve melhores resultados do que a acupuntura de forma isolada. Isso comprova que a acupuntura pode ser considerada uma opção a fim de minimizar os riscos de uma cirurgia ou auxiliar na recuperação do paciente
Keywords: Cão - Doenças; Coluna vertebral - Anomalias; Acupuntura veterinaria; Acupuncture; Electroacupuncture; Dogs